Osteoarthritis in women living in Cape Town: prevalence, characteristics, and the effects of a non-pharmacological intervention - Hendricks, Candice (Department of Health and Rehabilitation Sciences, 2022)
Osteoarthritis contributes to the burden of physical disabilities globally, as it is the most common cause of severe chronic pain impacting the function of millions of people. Osteoarthritis is more commonly reported by women who are obese and are physically inactive. These modifiable risk factors of obesity and lack of physical activity are also associated with other chronic diseases of lifestyle (CDL). A paucity of epidemiological data exists on the relationship between OA and CDL in women attending primary health care centres in Cape Town in South Africa, therefore, there was a need to further explore these inter-relationships to be able to plan and implement effective nonpharmacological management strategies to address the multidimensional health problem. To inform the development and implementation of a contextually relevant non-pharmacological intervention for women with osteoarthritis at primary health care level, several studies were conducted. The primary aim of this research project was to develop, implement and evaluate an evidence-based non-pharmacological rehabilitation intervention, advocating a patient-centred selfmanagement approach, for women with OA and CDL at primary health care centres in Cape Town. The literature review highlighted that a non-pharmacological intervention, consisting of selfmanagement principles, health education and exercise would be an effective management strategy for women with both OA and CDL. However, there is a dearth of high-quality randomised controlled trials investigating the effects of such interventions on function and health outcomes in women with OA and comorbidities at primary health care level in a South African context. Standardised outcome measures were selected and used to gather data for the different studies. The WHODAS 2 12-item questionnaire measured functional ability, EQ-5D-3L questionnaire measured health-related quality of life, Brief pain inventory (BPI) measured pain severity and pain interference, and Self-efficacy for Managing Chronic Disease 6-item Scale (SE-6) measured the level of confidence in managing chronic diseases were used and were available in English, Afrikaans, and isiXhosa languages. However, the COPCORD (survey about general health and osteoarthritis) and IPAQ (survey about physical activity levels) were not available in these languages and therefore needed crosscultural adaptation and translation.